A note on how to sell a network good - Raposo,Osorio Veiga A (International Journal of Industrial Organization, 2018)
I consider a monopolist in an industry with positive network externalities. The firm can screen heterogeneous consumers by offering multiple products. Screening captures a greater share of consumer surplus but also segregates consumers into multiple products, thereby lowering the total network surplus. Thus, screening is socially inefficient. I show screening is never profit maximizing: the monopolist offers a single product, but at an excessive price. Thus, excessive consumer segregation is unlikely to occur in industries such as online multiplayer games, financial exchanges and messaging software.